A Numerical Study on Leakage Flow in the Shroud Cavity of a Centrifugal Impeller - Jiaxi Chen; Zhitao Zuo; Jixiang Chen; Jianting Sun; Haisheng Chen (Energies)
A high-pressure centrifugal compressor with a shroud cavity is a key piece of energy equipment found in a compressed air energy storage (CAES) system. The leakage flow of the shroud cavity is an important factor affecting the efficiency of the system. Using systematic numerical studies, the influence of leakage flow on high-pressure centrifugal compressors under different leakage rates has been comprehensively elucidated. The study reveals that the leakage flow significantly increases the circumferential swirl angle of the flow at the impeller inlet, thereby exerting a significant influence on the flow characteristics within the impeller. As the leakage rate increases, the stable operating range of the compressor is significantly reduced, with the total pressure ratio decreasing by up to 2% and the isentropic efficiency dropping by up to 4 percentage points.